2005
DOI: 10.1038/sj.bjc.6602824
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oestradiol and tamoxifen on VEGF, soluble VEGFR-1, and VEGFR-2 in breast cancer and endothelial cells

Abstract: Angiogenesis is regulated by the balance between pro-and antiangiogenic factors. Vascular endothelial growth factor (VEGF), acting via the receptors VEGFR-1 and VEGFR-2, is a key mediator of tumour angiogenesis. The soluble form of the VEGF receptor-1 (sVEGFR-1) is an important negative regulator of VEGF-mediated angiogenesis. The majority of breast cancers are oestrogen dependent, but it is not fully understood how oestrogen and the antioestrogen, tamoxifen, affect the balance of angiogenic factors. Angiogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
55
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 32 publications
7
55
1
Order By: Relevance
“…Tamoxifen is a competitive antagonist of estrogen, but seems to have antiangiogenic effects independent of, and in addition to, estrogen receptor content or its anti-estrogen effects (Kousidoua et al, 2008). It have been reported that tamoxifen treatment of breast cancer, induces an antiangiogenic response by an efficient decrease of VEGF both in vitro and in vivo (Garvin and Dabrosin, 2003;Garvin et al, 2005;Nilsson and Dabrosin, 2006;Kumar et al, 2013;Rajput et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen is a competitive antagonist of estrogen, but seems to have antiangiogenic effects independent of, and in addition to, estrogen receptor content or its anti-estrogen effects (Kousidoua et al, 2008). It have been reported that tamoxifen treatment of breast cancer, induces an antiangiogenic response by an efficient decrease of VEGF both in vitro and in vivo (Garvin and Dabrosin, 2003;Garvin et al, 2005;Nilsson and Dabrosin, 2006;Kumar et al, 2013;Rajput et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This does not, however, rule out an estrogen-dependent regulation of IL-8 in less metastatic breast cancer cells. We have previously shown that VEGF secretion is increased by estradiol in MCF-7 cells although these cells express VEGF at very low levels (40,41). Very few studies have investigated direct effects on IL-8 secretion after estrogen exposure in hormone-dependent breast cancer models.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-estrogens, such as the synthetic, non-steroidal compound tamoxifen, and aromatase inhibitors, are cornerstones in the medical treatment of breast cancer. We have previously reported that tamoxifen treatment of experimental breast cancer, both in vitro and in vivo, induces an anti-angiogenic response [20,[24][25][26]. We recently showed that tamoxifen significantly up-regulated the expression and activity of MMP-9, whereas estradiol treatment decreased MMP-9 activity levels [20].…”
Section: Introductionmentioning
confidence: 99%